2013
DOI: 10.1371/journal.pone.0060732
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the Impact of Varicella Immunization on Herpes Zoster. A Model-Based Evaluation from Three European Countries

Abstract: The introduction of mass vaccination against Varicella-Zoster-Virus (VZV) is being delayed in many European countries because of, among other factors, the possibility of a large increase in Herpes Zoster (HZ) incidence in the first decades after the initiation of vaccination, due to the expected decline of the boosting of Cell Mediated Immunity caused by the reduced varicella circulation. A multi-country model of VZV transmission and reactivation, is used to evaluate the possible impact of varicella vaccinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 56 publications
4
73
0
Order By: Relevance
“…The paper focused on the 'fullboosting' hypothesis considered by recent public health modelling [12,13,15,17], according to which each re-exposure to varicella yields a CMI boosting event. As the exact magnitude of the boosting effect is still unclear [7] this might be debatable.…”
Section: Discussionmentioning
confidence: 99%
“…The paper focused on the 'fullboosting' hypothesis considered by recent public health modelling [12,13,15,17], according to which each re-exposure to varicella yields a CMI boosting event. As the exact magnitude of the boosting effect is still unclear [7] this might be debatable.…”
Section: Discussionmentioning
confidence: 99%
“…Only a fraction of contacts that would result in varicella infection in susceptible individuals lead to an effective immune boosting in VZVexperienced individuals. After recovery from HZ, individuals are assumed to become lifelong immune to new episodes of VZV reactivation [11][12][13][14]. Indeed, secondary HZ episodes, although possible, are relatively rare in immunocompetent individuals [2].…”
Section: (B) the Modelmentioning
confidence: 99%
“…Mathematical models of VZV transmission dynamics, all based on the exogenous boosting hypothesis, unanimously predict that mass immunization against varicella, which has been already introduced in some countries [15,16], including some regions of Spain [17], may result in a temporary increase of HZ incidence [12,13,18,19] as a consequence of the expected reduction of VZV re-exposures after vaccination. Nonetheless, empirical evidence coming from surveillance programmes of HZ provides ambiguous results, with some studies showing an increase of HZ following mass immunization and others not [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…This could be related to a temporal increase in the incidence of HZ, often occurring before the introduction of varicella vaccination programmes [11], as in Finland [11] and Germany [12]. In the United Kingdom, one study reported that the median age at HZ diagnosis was 62 years (interquartile range 48-73) [13].…”
mentioning
confidence: 99%